Antifungal activity of 6-substituted amiloride and hexamethylene amiloride (HMA) analogs - Vu, Kiem; Buckley, Benjamin J.; Bujaroski, Richard S.; Blumwald, Eduardo; Kelso, Michael J.; Gelli, Angie (Frontiers in Cellular and Infection Microbiology, 2023)
Fungal infections have become an increasing threat as a result of growing numbers of susceptible hosts and diminishing effectiveness of antifungal drugs due to multi-drug resistance. This reality underscores the need to develop novel drugs with unique mechanisms of action. We recently identified 5-(N,N-hexamethylene)amiloride (HMA), an inhibitor of human Na+/H+ exchanger isoform 1, as a promising scaffold for antifungal drug development. In this work, we carried out susceptibility testing of 45 6-substituted HMA and amiloride analogs against a panel of pathogenic fungi. A series of 6-(2-benzofuran)amiloride and HMA analogs that showed up to a 16-fold increase in activity against Cryptococcus neoformans were identified. Hits from these series showed broad-spectrum activity against both basidiomycete and ascomycete fungal pathogens, including multidrug-resistant clinical isolates.